KEPASTIAN HUKUM DALAM DIRECT INVESTMENT : STUDI KASUS PENCABUTAN IZIN TAMBANG DI KALIMANTAN TIMUR - Kurnia Fitri Rahma Dani; Sang Ayu Putu Rahayu (JURNAL ILMIAH NUSANTARA, 2025)
Direct investment in the mining sector plays an important role in driving economic growth, especially in resource-rich regions such as East Kalimantan. However, the government's policy of revoking Mining Business Permits (IUP) unilaterally and without a transparent mechanism has created considerable legal uncertainty for investors. This article examines the impact of this policy on the investment climate, focusing on the case of the revocation of 34 IUPs in East Kalimantan. Lack of transparency in the decision-making process and indications of corrupt practices reflect weaknesses in licensing governance, which directly affect investor confidence. Through a normative approach and juridical analysis, this article emphasizes the urgency of reforming mining licensing governance that upholds the principles of procedural justice, transparency and accountability. The recommendations put forward include simplifying licensing mechanisms, increasing stakeholder participation, and strengthening the role of independent supervisory institutions in order to create a healthy and sustainable investment climate in the national extractive sector.